Brand Image, Product Quality, dan Lifestyle Terhadap Keputusan Pembelian : Sepatu Bekas di toko Hi.corp Surabaya - Pujianingsih, Vonny Putri; Sari, Dewi Komala; Hariasih, Misti (Politeknik Piksi Ganesha Indonesia, 2025)
This study aims to determine the influence of brand image, product quality, and lifestyle on the purchasing decision of Thrifting Shoes at Hi.corp Surabaya. The research adopts a quantitative approach, with a descriptive method. The population in this study consists of Hi.corp customers who have made a minimum purchase of second-hand shoes at least once, with a sample size of 100. The sampling technique used is purposive sampling with the criteria of respondents being the Surabaya community aged between 17-30 years. Data collection is done through distributing questionnaires, and responses are measured using a Likert scale. The data analysis technique in this study utilizes the smart PLS (Partial Least Square) tool. The results of this study prove that Brand image affects the purchase decision of thrifting shoes products at Hi.corp Surabaya store, Product quality affects the purchase decision of thrifting shoes at Hi.corp store, and Lifestyle affects the purchase decision of thrifting shoes products at Hi.corp store.